FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR PAJAK (STUDI EMPIRIS WAJIB PAJAK ORANG PRIBADI NON KARYAWAN) - Sa’diah, Naila; Sari, Ria Nelly; Ratnawati, Vince (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2019)
This study aims to provide empirical evidence to examine the influence of knowledge and understanding of taxation regulations, tax socialization on the willingness to pay taxes. Influence of knowledge and understanding of tax regulations, tax socialization on awareness of paying taxes. The influence of tax awareness on the willingness to pay taxes. The influence of awareness of paying taxes as an intervening between knowledge and understanding of tax regulations, the effect of tax socialization on the willingness to pay taxes. As well as the influence of financial conditions and the effectiveness of the tax system as a moderation between awareness of paying taxes on the willingness to pay taxes. The population in this study were all non-employee personal taxpayers registered at the Senapelan Primary and Tax Service Office in Pekanbaru totaling 40,852 taxpayers. The minimum sample limit in this study according to the Slovin formula is 100 individual non-taxpayers. However, to strengthen respondents' responses, researchers distributed 150 questionnaires. The questionnaires were returned and 127 questionnaires could be used, the researchers increased the number of samples to 127 respondents, with sampling technique, convenience sampling. Data analysis in this study used Partial Least Square (PLS) approach. PLS is a model of Structural Equation Modeling (SEM) based on components or variants.The results of the study show that knowledge and understanding of taxation regulations do not directly affect the willingness to pay taxes. Tax socialization has a direct positive effect on the willingness to pay taxes. Knowledge and understanding of tax regulations have a direct positive effect on awareness of paying taxes. Tax socialization has a direct positive effect on awareness of paying taxes. Awareness of paying taxes has a direct positive effect on the willingness to pay taxes. Awareness of paying taxes mediates the relationship of knowledge and understanding of tax regulations with the willingness to pay taxes. Awareness of paying taxes does not mediate the relationship of tax socialization with the willingness to pay taxes. Financial conditions moderate the relationship of awareness of paying taxes with the willingness to pay taxes. The effectiveness of the tax system does not moderate the relationship of awareness of paying taxes with the willingness to pay taxes.